Small molecule inhibitors of the fosfomycin resistance enzyme FosM from Mycobacterium abscessus - Chiasson, Skye; Smith, Tatum; Bello, Landon; Chandrika, Nishad Thamban; Green, Keith D.; Garneau-Tsodikova, Sylvie; Thompson, Matthew K. (Biochimica et biophysica acta. General subjects, 2023)
Fosfomycin is a safe broad-spectrum antibiotic that has not achieved widespread use because of the emergence of fosfomycin-modifying enzymes. Inhibition of fosfomycin-modifying enzymes could be used to help combat pathogens like Mycobacterium abscessus. Our previous work identified several inhibitors for the enzyme FosB from Staphylococcus aureus. We have tested those same compounds for inhibition of FosM, the fosfomycin-modifying enzyme from M. abscessus. The work described here will be used as the basis for more detailed studies into the inhibition of FosM.